2011
DOI: 10.1063/1.3607444
|View full text |Cite
|
Sign up to set email alerts
|

A study of planar Richtmyer-Meshkov instability in fluids with Mie-Grüneisen equations of state

Abstract: We present a numerical comparison study of planar Richtmyer-Meshkov instability with the intention of exposing the role of the equation of state. Results for Richtmyer-Meshkov instability in fluids with Mie-Grüneisen equations of state derived from a linear shock-particle speed Hugoniot relationship (Jeanloz, J. Geophys. Res. 94, 5873, 1989; McQueen et al., High Velocity Impact Phenomena (1970) (2010)). Results for single and triple mode planar Richtmyer-Meshkov instability when a reflected shock wave occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…If one of the fluids is a liquid and the shock reflects off the interface, cavitation can occur when the pressure falls below the tensile strength of the liquid, further increasing the complexity of the problem. A recent numerical study of Ward and Pullin [18] looks into the role that the equation of state has on RM instability growth in a planar geometry. An experimental study by Buttler et al [19] investigates the RM instability at metal-vacuum interfaces in planar geometry.…”
Section: Introductionmentioning
confidence: 99%
“…If one of the fluids is a liquid and the shock reflects off the interface, cavitation can occur when the pressure falls below the tensile strength of the liquid, further increasing the complexity of the problem. A recent numerical study of Ward and Pullin [18] looks into the role that the equation of state has on RM instability growth in a planar geometry. An experimental study by Buttler et al [19] investigates the RM instability at metal-vacuum interfaces in planar geometry.…”
Section: Introductionmentioning
confidence: 99%
“…46, have been obtained [13], [47]. Numerical study of the RM instability in planar geometry had been reported for a Mie-Grüneisen equation of state [48].…”
Section: Introductionmentioning
confidence: 96%
“…This is currently an active area of research. 13 In general the theories are divided into two classes depending on the Atwood number. For positive Atwood numbers the incident shock travels from a low-density material to a higher density material.…”
Section: Linear Richtmyer-meshkov Growth Ratesmentioning
confidence: 99%